SEJARAH PELABUHAN SUNGAI DUKU DI KECAMATAN LIMA PULUH KOTA PEKANBARU TAHUN 1976-2019 - Fitria, Delta; Isjoni, Isjoni; Asril, Asril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Indonesia is known as an archipelago or also known as a maritime country. Therefore the role of ports is very vital in the Indonesian economy, such as the port in Pekanbaru City which is one of the ports that plays a very important role in the economic level in Pekanbaru City. The purposes of this writing are as follows: (1) To find out the history of the establishment of the Port Sungai Duku, Lima Puluh Subdistrict, Pekanbaru City. (2) To determine the function and role of Sungai Duku Port in improving the economy in Pekanbaru City. (3) To determine the development of Sungai Duku Port from 1976 to 2019. (4) To determine the factors causing the decline of the Port Sungai Duku. In this study, the author uses the historical method, namely by using the following methods: (1) Heuristics. (2) Verification. (3) Interpretation. (4) Historiography. The construction of the Sungai Duku Port had started in 1973 where in that year it had been installed for port construction and only finished in 1976. This port was originally built only for the port of commodity commodities for local people and passengers. However, later this port was officially become a passenger port in Lima Puluh District, Pekanbaru City.Key Words: Port Development History